Global justice, capabilities approach and commercial surrogacy in India - Saravanan, Sheela (Medicine, health care and philosophy, 2015)
Inequalities, ineffective governance, unclear surrogacy regulations and unethical practices make India an ideal environment for global injustice in the process of commercial surrogacy. This article aims to apply the ‘capabilities approach’ to find possibilities of global justice through human fellowship in the context of commercial surrogacy. I draw primarily on my research findings supplemented by other relevant empirical research and documentary films on surrogacy. The paper reveals inequalities and inadequate basic entitlements among surrogate mothers as a consequence of which they are engaged in unjust contracts. Their limited entitlements also limit their opportunities to engage in enriching goals. It is the role of the state to provide all its citizens with basic entitlements and protect their basic human rights. Individuals in India evading their basic duty also contribute to the existing inequalities. Individual responsibilities of the medical practitioners and the intended parents are in question here as they are more inclined towards self-interest rather than commitment towards human fellowship. At the global level, the injustice in transnational commercial surrogacy practices in developing countries calls for an international declaration of women and child rights in third party reproduction with a normative vision of mutual fellowship and human dignity.
Gesehen am 16.06.2020